Straw Mulching and Nitrogen Fertilization Affect Diazotroph Communities in Wheat Rhizosphere - Chen, Songhe; Xiang, Xiaoling; Ma, Hongliang; Penttinen, Petri; Zhao, Jiarong; Li, Han; Gao, Rencai; Zheng, Ting; Fan, Gaoqiong (Frontiers in Microbiology, 2021)
Diazotrophs that carry out the biological fixation of atmospheric dinitrogen (N2) replenish biologically available nitrogen (N) in soil and are influenced by the input of inorganic and organic substrates. To date, little is known about the effects of combined organic substrate addition and N fertilization on the diazotroph community composition and structure in purple soils. We investigated the effects of N fertilization and straw mulching on diazotroph communities by quantifying and sequencing the nifH gene in wheat rhizosphere. The abundance and richness of diazotrophs were greater the higher the fertilization level in the mulched treatments, whereas in the nonmulched treatments (NSMs), richness was lowest with the highest N fertilization level. The abundance and α-diversity of diazotrophs correlated with most of the soil properties but not with pH. At the genus level, the relative abundances of Azospirillum, Bacillus, and Geobacter were higher in the NSMs and those of Pseudacidovorax, Skermanella, Azospira, Paraburkholderia, Azotobacter, Desulfovibrio, Klebsiella, and Pelomonas in the mulched treatments. The differences in community composition between the mulched and the NSMs were associated with differences in soil temperature and soil organic carbon and available potassium contents and C:N ratio. Overall, straw mulching and N fertilization were associated with changes in diazotroph community composition and higher abundance of nifH gene in alkaline purple soils.